The Inclusion of Students as ‘Equal Partners’ in Higher Education; Implications for Assessment - Σπανάκη, Ειρήνη; Κατσαμποξάκη-Hodgetts, Κάλλια (Education Sciences, 2026)
The aim of this research is to explore students' views, before and after an educational intervention, on their understanding of their inclusion in higher education as 'equal partners'. In particular, their views were explored around: a) the parameters of the partnership, b) the parameters of their positive development through such a partnership, and c) the role of the lecturer in the positive outcome of the partnership. 66 students, from the Certificate of Pedagogical and Teaching Proficiency of the Faculty of Science and Engineering , University of Crete, completed a google form with corresponding questions. A significant difference in the students' attitudes was found after participation in the intervention in relation to 'understanding of the parameters related to partnership', and in particular regarding: (a) 'whether they feel that their suggestions for improving teaching are taken into account'; (b) 'whether they collaborate equally with teaching staff'; (c) 'whether their collaborations are full equal partnerships with teaching staff'; (d) 'feel that they are fully valued and respected in the decision-making process'; and (e) 'implementation of decisions'.